2016
DOI: 10.1186/s12931-016-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and the Pathophysiology of Asthma

Abstract: Asthma is a chronic respiratory disease whose prevalence is increasing in the western world. Recently research has begun to focus on the role the microbiome plays in asthma pathogenesis in the hope of further understanding this respiratory disorder. Considered sterile until recently, the lungs have revealed themselves to contain a unique microbiota. A shift towards molecular methods for the quantification and sequencing of microbial DNA has revealed that the airways harbour a unique microbiota with apparent, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 103 publications
1
52
0
1
Order By: Relevance
“…It may mean that bacterial lower airway inflammation acts as a complicating factor in patients with poorly controlled asthma as it was suggested previously. 22 An interesting finding of our study was the absence of a correlation between GI symptoms and food allergies with presence of esophageal eosinophils (with the exception of children with EoE), which emphasizes the importance of EsB in children with SUA even in the absence of clinical features suggestive of esophagitis. Emergence of aerodigestive medicine has been associated with the introduction of combined aerodigestive endoscopy in pediatric practice.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…It may mean that bacterial lower airway inflammation acts as a complicating factor in patients with poorly controlled asthma as it was suggested previously. 22 An interesting finding of our study was the absence of a correlation between GI symptoms and food allergies with presence of esophageal eosinophils (with the exception of children with EoE), which emphasizes the importance of EsB in children with SUA even in the absence of clinical features suggestive of esophagitis. Emergence of aerodigestive medicine has been associated with the introduction of combined aerodigestive endoscopy in pediatric practice.…”
Section: Discussionsupporting
confidence: 46%
“…More than half of our study, patients were found to have bacterial bronchitis with positive BAL cultures. It may mean that bacterial lower airway inflammation acts as a complicating factor in patients with poorly controlled asthma as it was suggested previously …”
Section: Discussionmentioning
confidence: 89%
“…5 Recent microbiome studies on the basis of culture-independent techniques, such as massive sequencing or microarrays, have shown that the lung is not sterile as previously thought. 6 Furthermore, it has been highlighted the role of bacteria residing in the human lung in the development of asthma and the severity of the disease, 7 and how bacteria interact with the airways in asthma susceptibility. 8 In addition, it has been shown that there is a connection between the inflammation of the airways and early environmental exposures in life, being those children who have had contact with animals and other allergens during their first period of life the ones less prone to develop the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively recent increase in asthma is attributed to the "hygiene hypothesis" of reduced exposure to microorganisms, a result of improved hygiene during infancy and early adulthood [4,5]. Reduced exposure to microorganisms during these vulnerable periods contributes to the development of lymphocytes with a T helper 2 (Th2) phenotype, i.e., lymphocytes known to promote asthmatic symptoms by producing Th2 cytokines, along with the induced accumulation of leukocytes.…”
mentioning
confidence: 99%